Incidental Detection of Intracranial Tuberculomas on 99mTc-TRODAT-1 SPECT/CT. (June 2015) - Tripathi, Madhavi; Arora, Geetanjali; Das, Chandan J.; Grover, Tripti; Gupta, Ranjan; Bal, Chandrasekhar
Abstract : Abstract: 99m Tc-TRODAT-1 has high affinity and specificity for dopamine transporters and is useful for the evaluation of presynaptic dopaminergic function, especially in parkinsonism. There have been a few reports of extrastriatal pathological accumulation of 99m Tc-TRODAT-1. We report a patient with intracranial tuberculomas that were incidentally detected when he underwent 99m Tc-TRODAT-1 scintigraphy for an unrelated indication.